Anne of Green Gables Based on a Novel by Lucy Maud Montgomery - Sullivan, Kevin Rodney; Ohashi, René; Follows, Megan; Dewhurst, Colleen; Farnsworth, Richard (Sullivan Entertainment, 2002)
Based on the novel that established Lucy Maud Montgomery as an important Canadian author, "Anne of Green Gables" wonderfully illustrates the picturesque innocence of Prince Edward Island during the early 1900s. Although a silent film, a musical, and even an animated series have tried to capture the childlike charm of her writing with varying degrees of success, Kevin Sullivan's made-for-TV production has become the definitive version, thanks to fabulous performances by Follows and Dewhurst. [www.gradingthemovies.com]
Keywords: DVD-Video